Simulation and Experimental Studies of A Mobile Robot for Underwater Applications - Doss, A.S.A. (Acta Press, 2021)
Due to increase in demand of autonomous vehicles in underwater applications, the modelling and control of underwater robots became primary importance in the design and development to improve their efficiency. In this article, a robotic underwater vehicle (RUV) is proposed for oceanographic purpose. First, the RUV model is developed using the Myring profile to produce the least drag force which supports the RUV to operate for a longer time with minimum force on the thruster. Second, the computational fluid dynamics (CFD) analysis is carried out to calculate the hydrodynamic effects of the proposed RUV. The k-Ïµ standard turbulence model is chosen for CFD analysis due to its good prediction capabilities. The ITTC 1957 correlation line equation is used to validate the CFDsimulated drag values of the RUV. Similarly, the lift and drag of the NACA0015 profile fin is calculated and validated. Third, a scaled-down model of the RUV is fabricated by considering the buoyancy, stability, pressure, propulsion, submerging and fineness ratio (L/D). The developed RUV is tested in a linear motion profile at velocities ranging from 0 to 1.25 m/s. The experimental results are compared with CFD and ITTC correlations, and it is found to be a minimum error band of 10. Further, balancing and leakage test are conducted and the developed RUV displayed neutrally buoyant characteristics with good stability. Â© 2021 BMJ Publishing Group. All rights reserved.